2009
DOI: 10.1093/aje/kwp167
|View full text |Cite
|
Sign up to set email alerts
|

Use of Supplements of Multivitamins, Vitamin C, and Vitamin E in Relation to Mortality

Abstract: In this cohort study, the authors evaluated how supplemental use of multivitamins, vitamin C, and vitamin E over a 10-year period was related to 5-year total mortality, cancer mortality, and cardiovascular disease (CVD) mortality. Participants (n = 77,719) were Washington State residents aged 50-76 years who completed a mailed self-administered questionnaire in 2000-2002. Adjusted hazard ratios and 95% confidence intervals were computed using Cox regression. Multivitamin use was not related to total mortality.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
61
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 37 publications
5
61
0
2
Order By: Relevance
“…Ascorbic acid (500 mg) slightly but non-significantly decreased the risk whereas beta-carotene had no effect. In their final conclusion, they said that neither of these nutrients had any positive or negative effect on the risk of the development of diabetes and that almost similar conclusion have been derived by Pocobelli et al (134) on supplementation of multivitamins, vitamin C and E in relation to mortality in cardiovascular disease and cancer. Likewise there are numerous reports claiming both favourable and adverse effects of antioxidant treatment and supplementation for an ideal health and for the treatment of human diseases.…”
Section: Antioxidant Therapy and Supplementssupporting
confidence: 52%
See 1 more Smart Citation
“…Ascorbic acid (500 mg) slightly but non-significantly decreased the risk whereas beta-carotene had no effect. In their final conclusion, they said that neither of these nutrients had any positive or negative effect on the risk of the development of diabetes and that almost similar conclusion have been derived by Pocobelli et al (134) on supplementation of multivitamins, vitamin C and E in relation to mortality in cardiovascular disease and cancer. Likewise there are numerous reports claiming both favourable and adverse effects of antioxidant treatment and supplementation for an ideal health and for the treatment of human diseases.…”
Section: Antioxidant Therapy and Supplementssupporting
confidence: 52%
“…In their concluding remarks in a review Clarke and Burnett (123) state that antioxidant supplementation should be avoided unless deficiency exist, lest they may lead to undesirable effects. Lately in 2009, Women's Antioxidant Cardiovascular Study (WACS) reported the influence of nutrient antioxidants on the risk of DMT-2 in women with high risk of cardiovascular diseases (134). Among 6574 women, 895 cases developed DMT-2 in 9.2 year follow up.…”
Section: Antioxidant Therapy and Supplementsmentioning
confidence: 99%
“…However, several studies could not find significant effectiveness of vitamin E on prevention of cancer, 4,7-25 reduction in cardiovascular diseases, 8,13,25-36 and overall mortality reduction. 5,15,19,25,27,[37][38][39] In a randomized, double-blind, placebo-controlled trial (The Physicians' Health Study II), a total of 14641 male physicians aging more than 50 years were enrolled. They received supplements of vitamin E (400 IU) every other day and were followed for 8 years.…”
Section: Vitamin E (α-Tocopherol)mentioning
confidence: 99%
“…Le caractere hydrophobe de la vitamine E lui permet de s'inserer dans les membranes biologiques riches en acides gras polyinsatures ou elle joue un rôle protecteur efficace en empêchant la propagation de la peroxydation lipidique induite par les especes reactives de l'oxygene (Traber et Atkinson, 2007 (Abner et al, 2011 ;Berry et al, 2009), ou montrent a l'inverse une diminution du risque de mortalite liee a des maladies cardiovasculaires (Pocobelli et al, 2009). Les validations chez l'homme restent donc tres difficiles a obtenir et sont pour l'instant sujet a controverse.…”
Section: Mode D'action De La Vitamine E : Le Debat Est Ouvertunclassified